Chronic recurrent multifocal osteomyelitis presenting with prolonged multifocal bone pain: a case report - Busappa, Karthik Perumachanahalli; Murali, Madhuvanthi; Ramakrishna, Manjushree; Swaraj, S. L. Akhila; Reddy, P. Shreyas (International Journal of Contemporary Pediatrics, 2026)
Chronic Recurrent Multifocal Osteomyelitis (CRMO) is an autoinflammatory bone disorder affecting primarily children and adolescents, characterized by sterile, recurrent bone pain and multifocal skeletal lesions. Diagnosis is based on clinical criteria and imaging, particularly MRI, to exclude infection or malignancy and to detect both symptomatic and clinically silent lesions. The pathogenesis involves dysregulation of the innate immune system and cytokine imbalance, contributing to chronic inflammation. We report a 13-year-old Indian girl with a prolonged 7-year history of intermittent multifocal bone pain and recurrent low-grade fever. Laboratory evaluation revealed elevated inflammatory markers with negative autoimmune and infective workup. MRI demonstrated multifocal medullary bone lesions consistent with non-infective osteitis. Based on clinical, laboratory, and radiological findings, a diagnosis of CRMO was established. The patient showed significant clinical improvement following treatment with NSAIDs and intravenous pamidronate. Early diagnosis and individualized treatment strategies are crucial in CRMO to improve outcomes and prevent long-term complications.